2017
DOI: 10.1002/art.40237
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Presence of Anti–Carbamylated Protein Antibodies in Early Arthritis With a Poorer Clinical and Radiologic Outcome

Abstract: Our findings indicate that anti-CarP antibodies are present in one-third of patients with early arthritis and in one-fourth of the RF-negative and ACPA-negative patients. They are particularly associated with a more severe radiographic outcome. Anti-CarP antibody positivity may help to accurately identify those at risk of erosive evolution in an early arthritis population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 33 publications
7
47
2
2
Order By: Relevance
“…We read with interest the article by Truchetet et al concerning the presence of anti–carbamylated protein antibodies (anti‐CarP) in patients with early arthritis from a French cohort. They found that anti‐CarP positivity was associated with higher disease activity and inflammation at baseline.…”
mentioning
confidence: 99%
“…We read with interest the article by Truchetet et al concerning the presence of anti–carbamylated protein antibodies (anti‐CarP) in patients with early arthritis from a French cohort. They found that anti‐CarP positivity was associated with higher disease activity and inflammation at baseline.…”
mentioning
confidence: 99%
“…However, in individuals who have already progressed to the stage of arthralgia, anti‐CarP did not have an additive value to ACPA and RF in predicting arthritis onset . Once disease has developed, the value of anti‐CarP regains its importance: The presence of anti‐CarP has been independently associated with higher disease activity at baseline and over time, as well as with radiographic damage . At baseline, a broad autoantibody profile regarding different isotypes of RF, ACPA, and anti‐CarP is associated with early treatment response; but the importance of this broad profile diminishes over time .…”
Section: Clinical Relevance Of Autoantibodies In Ramentioning
confidence: 97%
“…The presence of anti-CarP has been independently associated with higher disease activity at baseline and over time, 86,87 as well as with radiographic damage. 88,89 At baseline, a broad autoantibody profile regarding different isotypes of RF, ACPA, and anti-CarP is associated with early treatment response; but the importance of this broad profile diminishes over time.…”
Section: Clini C Al Rele Van Ce Of Autoantibod Ie S In R Amentioning
confidence: 99%
“…Another promising usage is the discrimination of patients with a poor prognosis. Anti-CarP Ab is a risk factor for future joint destruction independent of ACPA [1,[33][34][35][36][37]. A previous study reported that the anti-carbamylated albumin antibody was associated with a history of cardiovascular disease (CVD) [15] and anti-CarP Ab was associated with multiple indices of arteriosclerosis [38].…”
Section: Other Possibilities For Anti-carp Ab In Clinical Settingsmentioning
confidence: 99%